2016
DOI: 10.3892/etm.2016.3841
|View full text |Cite
|
Sign up to set email alerts
|

Picroside II protects myocardium from ischemia/reperfusion-induced injury through inhibition of the inflammatory response

Abstract: The inflammatory response is important in the pathogenesis of myocardial ischemia/reperfusion (I/R) injury. Picroside II, the primary active constituent of Picrorhizae, has been reported to protect the myocardium from I/R-induced injury, however, the exact mechanism underlying these protective effects remains unclear. The aim of the present study was to investigate the mechanism underlying the protective effects of picroside II on I/R-induced myocardial injury. Adult male Sprague-Dawley rats underwent 1 h left… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…In the present study, changes in the haemodynamic parameters supported ischemia-reperfusion injury in the normal rat heart (Li et al 2016). The enzymes routinely measured in the clinical laboratory for the purpose of diagnosing and monitoring myocardial infarction included creatine kinase (CK) and lactate dehydrogenase (LDH).…”
Section: Discussionmentioning
confidence: 83%
“…In the present study, changes in the haemodynamic parameters supported ischemia-reperfusion injury in the normal rat heart (Li et al 2016). The enzymes routinely measured in the clinical laboratory for the purpose of diagnosing and monitoring myocardial infarction included creatine kinase (CK) and lactate dehydrogenase (LDH).…”
Section: Discussionmentioning
confidence: 83%
“…Interesting, treatment with picroside II before ischemia was able to protect from I/R injury also the myocardium as showed by the decrease in infarct size, cardiomyocyte apoptosis and activity of CK and LDH. According to the authors, these effects were partly due to the inhibition of the HMGB1-RAGE/TLR2/ TLR4-NfkB signaling pathway (31). The same pathway has been found to be affected by ethyl pyruvate (EP).…”
Section: Figurementioning
confidence: 99%
“…Some literature pointed out that oral administration of the ethanol extract of RP could alleviate the myocardial damage caused by isoproterenol in rats, suggesting that RP had a certain protective effect on the heart (Senthil et al, ). Li et al () revealed that the pretreatment with picroside II could significantly alleviate I/R‐induced myocardial injury concomitantly with a decrease in inflammatory factor production. Picroside II also decreased the expression of high mobility group box1.…”
Section: Pharmacologymentioning
confidence: 99%